Introducing noncanonical amino acids for studying and engineering bacterial microcompartments. (June 2021) - Chen, Hao; Wilson, Jessica; Ottinger, Sara; Gan, Qinglei; Fan, Chenguang
Highlights: Genetic incorporation of noncanonical amino acids (ncAAs) can facilitate BMC studies and engineering. NcAAs with specific click chemistry functionality can be used to label BMC proteins by bioorthogonal reactions. NcAAs with photocrosslinking properties can help study the protein–protein interactions between BMC proteins. NcAAs with varied functional groups can be used to stabilize BMCs and modulate selective permeability of BMC shells. Abstract : Bacterial microcompartments (BMCs) with selectively permeable shells and encapsulated enzyme cores are well-suited candidates for nano-bioreactors because of their advantages of enhancing pathway flux and protection against toxic products. To better study and engineer protein-based BMCs, a series of protein chemistry approaches are adopted. As one of the most advanced techniques, genetic code expansion can introduce various noncanonical amino acids (ncAAs) with diverse functional groups into target proteins, thus providing powerful tools for protein studies and engineering. This review summarizes and proposes useful tools based on current development of the genetic code expansion technique towards challenges in BMC studies and engineering.